The effect of work area on work alienation among China’s grassroots judicial administrators - Nian Liu; Meiling Zhang; Boya Feng (Scientific Reports, 2022)
Abstract Work alienation refers to mental self-separation from work, and it is an integral reflection of workers and their work. Few studies have explored the association between work area and work alienation among grassroots judicial administrators. A stratified sampling method was used to collect data from 288 grassroots judicial administrators in Guangzhou to measure the overall status quo and work alienation in this group. This study found that the current grassroots judicial administrative team has a reasonable structure, high professional quality, and rich grassroots work experience, but a high level of work intensity (Mean = .667) and a lack of autonomy (Mean = .757) are prominent. Work area (unstandardized regression coefficient, B = .917) is significantly related to work alienation when controlling for sociodemographic and work characteristic variables: the closer the work area is to the city centre areas, the higher the level of work alienation. In addition, education level also has a significant effect on work alienation: the lower the individual education level is, the stronger the work alienation. The discussion focuses on the knowledge needs in grassroots judicial administrative work and the importance of the external working environment, and further research implications are proposed.